Interrelación De La Utilización De Las Técnicas De Aprendizaje Y Su Consecuencia En El Rendimiento Escolar De Niños/As De La Escuela De Educación Inicial “Guillermo Arosemena Coronel” Cantón Puebloviejo, Provincia De Los Ríos” - Zúñiga Coello, María (2015)
The study of the relationship of using learning techniques and its consequence on the academic performance of students of the school of basic education "Colonel Guillermo Arosemena" Puebloviejo canton, Los Rios province, aims to determine the level of performance of pupils of that educational unit and what the techniques used by teachers to impart knowledge and create new educational concepts are. The specific area of research is the school of basic education "Colonel Guillermo Arosemena" Pueblo Viejo Canton, in this institution working 19 teachers, 1019 students distributed in existing grades, the predominant economic activity to cover the family expenses is farming. We consider of vital importance to study this issue, as it will allow us to discover the reason for the poor school performance and fight it using appropriate methods that are within our reach, considering that school is not the only institution responsible for the low school performance of young people. The general problem of the research is How learning techniques influence the academic performance of students of early childhood education at the School of Basic Education "Colonel Guillermo Arosemena" Canton Puebloviejo ?, being the objective of this research is whether learning techniques influence the academic performance of students of students starting school education basic education "Colonel Guillermo Arosemena" Puebloviejo Canton. One of the conclusions refers to the use of various learning strategies and active methodologies allow the continued collective participation of students individually and which leads to their academic performance is optimal and thus achieve the capacities provided.